الوكالة الأخلاقية للروبوت ومسئولية اتخاذ القرار: دراسة في أخلاقيات الآلة والذكاء الاصطناعي - عبدالفتاح، السيد عبدالفتاح جاب الله (جامعة القاهرة - فرع الخرطوم - كلية الآداب, 2023)
لقد أحدثت التطورات الأخيرة في تقنيات الذكاء الاصطناعي اهتماما كبيرا من قبل وسائل الإعلام وعامة الناس، لاسيما مع ظهور الروبوتات الذكية المتطورة التي تمتلك القدرة على محاكاة السلوك الإنساني. فقد شهدت غالبية دول العالم تقدما واسعا ومذهلا وسريعا في مجال تكنولوجيا الروبوتات، حيث بدأ الروبوت يدخل في مجالات الحياة اليومية كافة؛ مثل: التصنيع، والرعاية الصحية، والدفاع، والفضاء، والمجالات الخدمية والمنزلية، وغيرها. مما جعل بعض الخبراء يتوقعون أن تصبح الروبوتات في المستقبل القريب من الحاجات اليومية الضرورية للمجتمع البشرى. ونظرا لأن تقنيات الذكاء الاصطناعي مثل (الروبوتات وروبوتات الدردشة والصور الرمزية والوكلاء الأذكياء الآخرين) تنتقل من كونها مجرد أدوات إلى أن تصبح وكلاء مستقلين وزملاء في الفريق، فإن التركيز المهم للبحث والتطوير هو فهم التأثير الأخلاقي لهذه التقنيات ومدى مسئوليتها عن قراراتها وأفعالها تهدف هذه الدراسة لمناقشة موضوع الوكالة الأخلاقية للروبوت لمحاولة الكشف عن مدى إمكانية أن يصبح الروبوت وكيلا أخلاقيا، أي قادرا على التصرف واتخاذ قرارات عقلانية فيما يتعلق بالسلوك الأخلاقي، وهل سيكون الروبوت مسئولا أخلاقيا عن نتيجة قراراته وأفعاله أم لا؟ وماذا ستكون العواقب البشرية المحاولة أتمتة صنع القرار الأخلاقي؟ والوقوف على دراسة القضايا والإشكاليات التي ارتبطت بهذا المشروع، والإسهام في توضيح الجهود المبذولة فيه ومدى جدواها والتحديات التي تواجهه. Recent advancements in artificial intelligence (AI) technologies have sparked significant interest among the media and the general public. especially with the emergence of advanced intelligent robots that have the ability to simulate human behavior. The majority of countries in the world have witnessed a wide, amazing and rapid progress in the field of robotics technology, as the robot has begun to enter all areas of daily life, Such as manufacturing, healthcare, defense, space exploration, service industries, and even households. Consequently, experts anticipate that robots in the near future will become an essential part of human society's everyday needs. As AI technologies (e.g. robots, chatbots, avatars and other intelligent agents) move from being mere tools to becoming autonomous agents, an important focus of research and development is understanding the ethical impact of these technologies and their responsibility for their own decisions. This study aims to discuss the issue of the ethical agency of the robot to try to reveal the extent to which the robot can become a moral agent, that is, capable of acting and making rational decisions regarding ethical behavior, and will the robot be morally responsible for the outcome of its decisions or not? And what would be the human consequences of trying to automate moral decision-making? And standing on the study of issues and problems associated with this project and contributing to the clarification of the efforts made in it and the extent of their feasibility and the challenges they face.
Keywords: الذكاء الاصطناعي -- أخلاقيات الروبوت -- الوكالة الأخلاقية -- الوكلاء الأخلاقيون